Abbas Khider - Coury, David N.,Machtans, Karolin (Peter Lang Ltd. International Academic Publishers, 2021)
Abbas Khider has established himself as one of the leading literary voices of refugees and marginalised communities in Germany today.Born in Baghdad, Iraq, hs novels probe important questions related to political, cultural, and linguistic identity. This volume represents the first collection of essays devoted to Khider's works to date.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Electronic books; Khider; Abbas